Traditional Skirts of the Tai Dam Ethnic Group in Nathong Village, Kham District, Xieng Khouang Province - Phetsamai, Somsack; VONGPHACHANH, Phitsaphong; KEOMANY, Thongsouk; PANYVONG, Sommor; PHENGPHANYA, Phone; LATSIMMA, Palidtha; SIMMALAVONG , Kheuavan (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This article studies the traditional skirts (Sin) of the Tai Dam ethnic group in Nathong Village, Kham District, Xieng Khouang Province. The objective is to examine the production processes and the meanings of the textile patterns. This qualitative research employed interviews, observations, and data analysis. Data were collected from 8 Tai Dam textile experts, revealing three stages of production and two categories of symbolic meanings. The research tools included interview guides and observation forms, The result found that: The production process of Tai Dam skirts in Kham District consists of three main components: raw materials for weaving, dyeing processes for cotton and silk, and the use of traditional equipment. Raw material production includes cotton cultivation, sericulture (mulberry cultivation and silkworm rearing), the planting of indigo and Hom plants, and the use of other natural materials (stick lac, turmeric, tree bark, etc.). The dyeing process involves both indigo/hom dyeing and the use of various natural raw materials. Weaving equipment includes the loom (Ki), reed (Pheurm), loom bench, warp, temple (Mai Kampan), shuttle slats, heddles (Kao Yerng and Kao Noy), pattern-storing sticks, treadles, swift, spinning wheel (La), shuttle, bobbins, and bobbin baskets. The meanings of Tai Dam textile patterns are categorized into two types: patterns representing living beings and patterns based on imagination and beliefs, such as the Water Bug (Maeng Da) motif, the Sky God Riding a Lion (Phya Then Khi Sing) motif, and the Small Naga (Nark Noy) motif.